Influence of barometric pressure on interleukin-1β secretion - Becker, William J.; Cannon, Joseph G. (American journal of physiology. Regulatory, integrative and comparative physiology, 2001)
Monocytes and macrophages are activated by various environmental challenges, including microorganisms, radiation, and pollutants. These cells release cytokines, such as interleukin (IL)-1β, that mediate physiological adaptations to stress. This study sought to define further the role of IL-1β in general adaptation to environmental stress by testing the hypothesis that high altitude (20,000 ft, 6,096 m) would stimulate IL-1β secretion from isolated human blood mononuclear cells. Cells from six young men (aged 22–26 yr) were divided into separate cultures incubated in either standard ambient conditions or in one of three test conditions, hypobaric hypoxia (simulating 20,000 ft), hypobaric normoxia (20,000 ft, O 2 supplemented), and normobaric hypoxia (10% O 2 ). This design allowed differentiation between pressure-related vs. oxygen-related effects. Each subject made multiple blood donations in order that cells from all subjects were tested in all conditions. Contrary to the hypothesis, IL-1β secretion was not induced at simulated altitude in basal cell cultures. In lipopolysaccharide-stimulated cell cultures, exposure to altitude inhibited IL-1β secretion by ∼40%, and the inhibition was due to the change in pressure ( P = 0.039) rather than the change in oxygen. Secretion of other factors (IL-1 receptor antagonist and soluble IL-1 receptor type II) was not inhibited. Although these results are in opposition to the original hypothesis, they provide insight regarding adaptations necessary for hematopoiesis in response to high altitude and also provide a cellular rationale for the mountain sanatoriums of the 19th and early 20th centuries.